Plan general integral de mantenimiento para la infraestructura física del Hospital Dr. Tomás Casas Casajús - Barboza-Arguedas, Marlon (Instituto Tecnológico de Costa Rica, 2013)
This study focuses on proposing a preventive maintenance plan and their routines, for the physical infrastructure on Dr. Tomás Casas Casajus Hospital, in addition to an analysis of conservation investments to take advantage of all resources available for these activities the most accurate and efficient way. Before establishing the activities comprising the proposed maintenance plan, data was collected from the impact of maintenance, use of man-hours, costs, etc., plus an analysis of the current status of each of the buildings and electromechanical systems. From this information it was concluded that maintenance activities currently carried out are mostly to address repairs or corrective maintenance, these are consuming approximately 63.08%, versus 36.92% of total man hours that were used during 2012 in preventative maintenance activities. Investments made in the maintenance of infrastructure and facilities for the same year reached a value of ₡ 155,943,614, of these, 51.91% was spent on corrective maintenance while 48.09% for preventative maintenance. Conservation investments today are good, so a target in the medium and long term is to lower the percentage of corrective maintenance and utilize human and financial resources in the best way possible.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2013.
Keywords: Conservación; Mantenimiento Correctivo; Mantenimiento Preventivo; Mantenimiento Predictivo; Rendimientos; Capacidad Operativa